(untitled) (ModaPalavra e-periódico, 2024)
Based on the premise that fashion expresses regional identities and cultures through clothing, this article aims to analyze how artisanal and artistic elements associated with the culture of the state of Minas Gerais have been used as conceptual and visual references by stylists/brands showcased at São Paulo Fashion Week. The methodology employed was qualitative research, specifically exploratory-descriptive, conducted through a semiotic analysis of images from three collections by different stylists/brands: Renato Loureiro (2005), Acquastudio (2014), and Ronaldo Fraga (2018). These collections drew visual inspiration from traditional elements of Minas Gerais, notably featuring the use of artisanal techniques such as “fuxicos” and knits observed in Loureiro’s collection, and embroideries crafted by artisans from the city of Mariana in Fraga’s pieces. Additionally, a woven dialogue with Minas Gerais’ baroque art was observed in Acquastudio’s designs. By incorporating elements of culture from diverse regions into fashion, the article reaffirms the notion of cultural diversity within the country.